Analisis Yang Mempengaruhi Auditor Switching (Studi Kasus pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2016 – 2018) - Made Wedaswari; Gustita Arnawati Putri; Sari Widati; Anggun Meira Bella (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
The purpose of this research is to find analysis that affect auditor switching (acase studi on a manufacturing company listed on Indonesian stock exchange 2016-2918. These factors are audit opinion, management turnover, KAP size, client’s size, and audit tenure. This topic was chosen because there are several companies in Indonesia to do Voluntary Auditor Switching and not in accordance with government regulations. Population in this research are all manufacture companies listed in Indonesia Stock Exchange (BEI) during 2010-2015. Data collecting method which used in this research is purposive sampling. A total 65 manufacturing company are used as sample firms. Hypothesis in this research are tested by logistic regression analysis with SPSS 22 software. Based on the results, variables that influence auditor switching are management turnover (CEO) and KAP Size (KAP). Audit opinion (OPINI), client’s size (LNTA) and Audit Tenure (TENURE) have no effect to Auditor Switching.